Pendidikan Islam dalam Memperkuat Kerukunan Umat Beragama di Desa Kapuan Blora: Penelitian - Nurul Faiqoh; H. Muhammad Najib (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study examines the role of Islamic education in strengthening religious harmony in Kapuan Village, which maintains social harmony despite its religious diversity. Using a qualitative descriptive method, data were gathered through observation, interviews, and documentation. The results show that Islamic education is applied through madrasah, recitation, curriculum with multicultural values, and interfaith dialog. It serves not only to transmit religious teachings but also to foster social cohesion and interfaith interaction. Supporting factors include active religious leaders, deliberative culture, and cooperation programs, while challenges involve stereotypes and prejudice. The study concludes that Islamic education significantly contributes to harmony and can be a model for other multicultural communities.